GAYA KEPEMIMPINAN, BUDAYA ORGANISASI, MOTIVASI KERJA, WORK-LIFE BALANCE PENGARUHNYA TERHADAP KINERJA ANGGOTA KORPS BRIMOB POLRI PANIKI DUA, KOTA MANADO, SULAWESI UTARA - Alwi, Rassya Devita; Lucky O. H. Dotulong; Irvan Trang (Magister Manajemen Program Pasca Sarjana Universitas Sam Ratulangi Manado, 2025)
This study aims to analyze the influence of Leadership Style, Organizational Culture, WorkMotivation, and Work–Life Balance on the Performance of the Brimob Corps Members ofPaniki Dua in Manado City, North Sulawesi. The background of this research stems from theneed to understand the dynamics of police officers’ performance, which is shaped by variousinternal and external organizational factors. The performance of police personnel—especiallyBrimob members who face high-risk duties—depends greatly on the leadership patternsapplied within the unit, the strength of the organizational culture, the level of workmotivation, and the members’ ability to balance demanding job responsibilities with theirpersonal lives. Therefore, this study is crucial for providing empirical insights into the keyfactors that determine performance improvement in the field.The research employed a quantitative approach using survey techniques, with questionnairesdistributed to 100 Brimob members as the research sample. The collected data were thenanalyzed using the Statistical Product and Service Solutions (SPSS) software to examinestatistical relationships and effects among the variables. This approach was chosen to ensureobjective, measurable, and scientifically accountable results. The findings show thatLeadership Style has a significant but negative influence on member performance. Thisindicates that the leadership approach currently applied has not fully succeeded in enhancingperformance and may even create pressure or discomfort among members. In contrast,Organizational Culture is found to have a significant and positive effect on performance,demonstrating that a conducive work environment, strong organizational values, and well-structured work systems can effectively enhance members’ productivity.Keywords: Leadership Style, Organizational Culture, Work Motivation, Work-Life Balance,Performance, SPSS – IBM SPSS software